A Case of Vein of Galen Aneurysmal Malformation Diagnosed Prenatally in a Monochorionic-Diamniotic Twin Pregnancy - Berger, Dana Senderoff; Robinson, Andre; Chervenak, Judith; Thomas, Kristen; Srinivasan, Ranjini; Sharma, Geeta; Roman, Ashley S.; Penfield, Christina A.; Limaye, Meghana (American Journal of Perinatology Reports, 2024)
We present a case of a vein of Galen aneurysmal malformation (VGAM), a rare congenital arteriovenous malformation, in one fetus of a monochorionic-diamniotic twin pregnancy. The diagnosis was made with color Doppler ultrasonography at 28 weeks and the affected fetus was found to have worsening cardiomegaly on subsequent fetal echocardiograms. She was emergently delivered at 32 weeks for abnormal fetal heart rate tracing of the affected twin. Magnetic resonance imaging of the brain findings after delivery demonstrated severe neurological injury; therefore, postnatal embolization was not performed. The neonate died on day of life 9. The cotwin survived without neurological complications. This is the first case in the literature of a VGAM diagnosed prenatally in a monochorionic-diamniotic twin pregnancy and demonstrates the challenge of delivery timing with prenatal diagnosis in a twin pregnancy.
Keywords: twin anomaly; twin pregnancy; vein of Galen aneurysmal malformation